If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -15 = 30 + 2x Reorder the terms: -15 + 8x = 30 + 2x Solving -15 + 8x = 30 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -15 + 8x + -2x = 30 + 2x + -2x Combine like terms: 8x + -2x = 6x -15 + 6x = 30 + 2x + -2x Combine like terms: 2x + -2x = 0 -15 + 6x = 30 + 0 -15 + 6x = 30 Add '15' to each side of the equation. -15 + 15 + 6x = 30 + 15 Combine like terms: -15 + 15 = 0 0 + 6x = 30 + 15 6x = 30 + 15 Combine like terms: 30 + 15 = 45 6x = 45 Divide each side by '6'. x = 7.5 Simplifying x = 7.5
| 10(z+1)-2(z-4)=4(z-4)+3(z-2) | | 6(x+7)-25=0 | | 111=7(1+5x)-1 | | 9c=8 | | 21(2y+1)=0 | | [x-7]x[x-4]=0 | | 6(r+6)=6(r+8) | | 6z=2.5 | | 3(3r-5)=-87 | | 0.6m+1.4+0.04m=14.2 | | 3(7x-3)+4(13-3x)-4(2x+5)=-5 | | 3x^2+84x+153=0 | | 4-2y-y=1y | | 7+4(5x-5)=5-4(2x+1) | | 0.1x^2+0.7x=3 | | 6(8-7p)=384 | | 9-x+3x-2-8x=0 | | P=qv/he | | 3[7-(-2x-4)]=42x+105 | | -x^2+14x=43 | | -2(-2x+8)=-2 | | 3[7-(-2x-4)]=4x+105 | | 102=2+5(8+6m) | | -3(2v+9)-3(3v-7)=4v+6(2v-8) | | 2x-7+8x-6+0.2x-5+0.04x-4+0.06x-3+0.254x-2+0.01x-1-2=0 | | 35=6x-x | | 65-(45-20)=(65-45)-20 | | 3.3y=3 | | 5x/2)-9=(2x-7/6) | | 5y-2=9y+22 | | (3x+42)+(x+34)=180 | | 2(x+3)=7(x-1)-12 |